Expression profiles and functions of ferroptosis-related genes in intimal hyperplasia induced by carotid artery ligation in mice - Zhang, Lina; Li, Wei; Shi, Bo; Zhang, Xiaoqing; Gong, Kaizheng (Frontiers in Genetics, 2022)
Intimal hyperplasia (IH) is a prominent pathological event that occurs during in-stent restenosis and atherosclerosis. Ferroptosis, characterized by iron-dependent and lipid peroxidation, has become the recent focus of studies on the occurrence and progress of cardiovascular diseases. However, there are few studies on ferroptosis and IH. Therefore, we aimed to identify and validate ferroptosis-related markers in IH to explore new possibilities for IH diagnosis and treatment. The IH microarray dataset (GSE182291) was downloaded from the Gene Expression Omnibus (GEO) database and ferroptosis-related genes (FRGs) were obtained from the FerrDb databases. The differentially expressed genes (DEGs) were analyzed using the GEO2R. Overlapping was performed to identify the ferroptosis-related DEGs among the DEGs and FRGs. Then, clustering, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, and protein–protein interaction (PPI) analyses were performed. Subsequently, the hub genes were identified using Cytoscape and hub gene–transcription factors and hub gene–microRNA networks were constructed. Finally, real-time qPCR (RT-qPCR) and immunohistochemistry (IHC) were used to verify the mRNA and protein levels of the hub FRGs in IH. Thirty-four FRGs showing significantly different expression were identified from a total of 1,197 DEGs 2 days after ligation; 31 FRGs were selected from a total of 1,556 DEGs 14 days after ligation. The GO and KEGG analyses revealed that these 34 ferroptosis-related DEGs identified 2 days after ligation were mainly enriched in the basolateral plasma membrane, ferroptosis, lipid and atherosclerosis, and IL-17 signaling pathways. The 31 ferroptosis-related DEGs in endometrial hyperplasia identified 14 days after ligation were mainly enriched in response to oxidative stress, ferroptosis, tumor necrosis factor signaling pathway, and lipid and atherosclerosis. Five hub FRGs (Il1b, Ptgs2, Cybb, Cd44, and Tfrc) were identified using PPI networks; four hub FRGs (Il1b, Ptgs2, Cybb, and Cd44) were validated to be upregulated 2 and 14 days after ligation using RT-qPCR and show significantly different expression 14 days after ligation via IHC. Our findings verify the expression of hub DEGs related to ferroptosis in IH and elucidate the potential relationship between ferroptosis and IH, providing more evidence about the vital role of ferroptosis in IH.